2012
DOI: 10.1016/j.janxdis.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Positive thinking in anxiety disordered children reconsidered

Abstract: Negatively valenced thoughts are assumed to play a central role in the development and maintenance of anxiety. However, the role of positive thoughts in anxiety is rather unclear. In the current study we examined the role of negative and positive self-statements in the anxiety level of anxious and non-anxious children. Participants were 139 anxiety disordered children and 293 non-anxious children (8-18 years). Compared to non-anxious children, anxious children reported more negative thoughts, less positive tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(58 reference statements)
1
10
0
3
Order By: Relevance
“…Cognitive processes have been accorded a pivotal role in the etiology, treatment, maintenance, and remission of depression [51][52][53]. Cognitions play an important role in theories about the development and treatment of anxiety disorders [21]. Often activated by negative and stressful life events, negative automatic thoughts are often repetitive and intrusive, which play a key role in precipitating psychopathology [54].…”
Section: Automatic Thought In Cognitive-behavioral Therapy (Cbt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive processes have been accorded a pivotal role in the etiology, treatment, maintenance, and remission of depression [51][52][53]. Cognitions play an important role in theories about the development and treatment of anxiety disorders [21]. Often activated by negative and stressful life events, negative automatic thoughts are often repetitive and intrusive, which play a key role in precipitating psychopathology [54].…”
Section: Automatic Thought In Cognitive-behavioral Therapy (Cbt)mentioning
confidence: 99%
“…Negative thinking has been found to play a pivotal role in psychopathological states such as depression [3,11,[13][14][15][16][17][18] and anxiety [3,7,[17][18][19][20][21]. Indeed, studies have found a connection between the presence of negative thoughts and anxiety in clinically anxious adults [22] and children [23].…”
Section: Introductionmentioning
confidence: 99%
“…Contents related to affection in children's thoughts were also observed in the construction process of the Children's Automatic Thoughts Scale (CATS) [40], although that kind of items were removed during the development of the scale's dimensions. Many studies concerning this topic address the cognitive characteristics related to anxiety, even if they do not consider the assessment of the emotional component [25,40,41]. Consequently, the results of the present study raise some questions about the strategies that are being used to study children's cognitive products when the expression of emotions is not considered and how the derived information may be incomplete or biased.…”
Section: Contens Of Expressed Emotionsmentioning
confidence: 85%
“…positive cognitive products) has been focused only on their quantification, aiming at analysing their frequency in children with different levels of anxiety [25][26][27]. The present work has contributed to surpass the need of more extensive knowledge on positive thoughts pointed out by previous studies [11,16,25], presenting the several contents founds and discussing them in light of the available literature.…”
Section: Contents With Positive Valence and Characteristics Of Normatmentioning
confidence: 94%
See 1 more Smart Citation